2021
DOI: 10.15869/itobiad.870549
|View full text |Cite
|
Sign up to set email alerts
|

The Relatıon Of Domestıc Income Wıth Urbanızatıon And Energy Consumptıon: Turkey Sample

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…According to this view, supportive energy policies will contribute to economic growth. Aslan (2021), Demirgil andBirol (2020), Turkmen et al (2018), Çınar andOz (2017), Cağıl andTürkmen (2013), Saatçi and Dumrul (2013), Mucuk and Uysal (2010) reached conclusions in their analysis for Türkiye that an increase in EC increases EG. In a sectoral study for Türkiye, Koç (2020) concluded that the use of energy used in the transportation, industry and services sectors has a positive effect on growth, while the energy used in the agricultural sector does not affect economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to this view, supportive energy policies will contribute to economic growth. Aslan (2021), Demirgil andBirol (2020), Turkmen et al (2018), Çınar andOz (2017), Cağıl andTürkmen (2013), Saatçi and Dumrul (2013), Mucuk and Uysal (2010) reached conclusions in their analysis for Türkiye that an increase in EC increases EG. In a sectoral study for Türkiye, Koç (2020) concluded that the use of energy used in the transportation, industry and services sectors has a positive effect on growth, while the energy used in the agricultural sector does not affect economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%